A study of Ramadan effect on the Indonesia Stock Exchange - Saputro Ahmad, Bimo Galuh; Utami, Wiwik (Management and Entrepreneurship: Trends of Development, 2019)
This study aims to test whether there are significant anomalies in stock returns in Shaaban (before Ramadan), Ramadan, and Shawwal (after Ramadan) in the Indonesia Stock Exchange (IDX). Sample was selected based on the listed companies included in the Liquid 45 indices (LQ45). Data collection is based on weekly closing price in the period 2012 till 2017. Research design followed the event studies and assumes that capital market was semi strong. The analytical method is the Wilcoxon-test and Paired Sample T-test statistical models with a confidence level of 95% or α = 0.05. The results showed that there was no significant statistical difference between LQ45 returns and abnormal returns in Shaaban, Ramadan, and Shawwal in the research period. It revealed that there was not any anomalies effect of Ramadan in Indonesia Stock Exchange. JEL Classification: H54, R53